A bibliography on menstrual regulation and abortion studies in Bangladesh - Akhtar, Halida Hanum; Ferdous Khan, Tabassum; Bangladesh Institute of Research for Promotion of Essential & Reproductive Health and Technologies (Dhaka : Bangladesh Institute of Research for Promotion of Essential & Reproductive Health and Technologies (BIRPERHT), 1996)
Contributed articles.
Includes bibliographical references.
Keywords: Abortion -- Bangladesh; Abortion -- Bangladesh -- Bibliography; Menstrual regulation -- Bangladesh; Menstrual regulation -- Bangladesh -- Bibliography